Dental Care and Education Facing Highly Transmissible SARS-CoV-2 Variants: Prospective Biosafety Setting: Prospective, Single-Arm, Single-Center Study - Thurzo, Andrej; Urbanová, Wanda; Waczulíková, Iveta; Kurilová, Veronika; Mriňáková, Bela; Kosnáčová, Helena; Gális, Branislav; Varga, Ivan; Matajs, Marek; Novák, Bohuslav (International journal of environmental research and public health, 2022)
With the arrival of the highly transmissible Omicron variants (BA.4 and BA.5), dentistry faces another seasonal challenge to preserve the biosafety of dental care and education. With the aim of protecting patients, students, teachers and healthcare professionals, this paper introduces a prospective sustainable biosafety setting for everyday dental care and education. The setting developed by dental clinicians, epidemiologists, and teachers of dentistry consists of a combination of modern technologies focused on the air-borne part of the viral pathway. The introduced biosafety setting has been clinically evaluated after 18 months of application in the real clinical environment. The protocol has three fundamental pillars: (1) UVC air disinfection; (2) air saturation with certified virucidal essences with nebulizing diffusers; (3) complementary solutions including telehealth and 3D printing. A pseudonymous online smart form was used as the evaluation method. The protocol operates on the premise that everybody is a hypothetical asymptomatic carrier. The results of a clinical evaluation of 115 patient feedbacks imply that no virus transmission from patient to patient or from doctor to nurse was observed or reported using this protocol, and vice versa, although nine patients retrospectively admitted that the clinic visit is likely to be infectious. Despite these promising results, a larger clinical sample and exposition to the current mutated strains are needed for reliable conclusions about protocol virucidal efficiency in current dental environments.
Keywords: virucidal oil dispersion; sustainability; Humans; dental education; UVC; lidé; dentistry; Dental Care; prospektivní studie; prevention; stomatologická péče; COVID-19; biosafety; Prospective Studies; Containment of Biohazards; Retrospective Studies; teledentistry; retrospektivní studie; orthodontics; omezování biologických rizik; SARS-CoV-2; infection